Functionally distinct high and low theta oscillations in the human hippocampus - Abhinav Goyal (Nature Portfolio, 2020)
We show that the human hippocampus exhibits two distinct theta oscillations during spatial navigation with the faster oscillation in posterior regions showing movement modulation. This result suggests a distinct feature of the human hippocampus compared to rodents, which generally show a single 8 Hz rhythm.